2021
DOI: 10.3390/microorganisms9091991
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease-Related Mortality in Spain, 1997 to 2018

Abstract: Background. Chagas disease (CD) is associated with excess mortality in infected people in endemic countries, but little information is available in non-endemic countries. The aim of the study was to analyze mortality in patients admitted to the hospital with CD in Spain. Methods. A retrospective, observational study using the Spanish National Hospital Discharge Database. We used the CD diagnostic codes of the 9th and 10th International Classification of Diseases to retrieve CD cases from the national public re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Prior studies have been performed on this registry for other illnesses, including infectious diseases. They have recognised its high value for producing estimates of current burden and time trends for different clinical conditions at the national level 12–15 . Given that the Spanish health system provides universal coverage, even for illegal migrants, biases due to difficulties in access to care should be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have been performed on this registry for other illnesses, including infectious diseases. They have recognised its high value for producing estimates of current burden and time trends for different clinical conditions at the national level 12–15 . Given that the Spanish health system provides universal coverage, even for illegal migrants, biases due to difficulties in access to care should be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…In endemic areas, the analysis of CD prevalence in cancer patients revealed a notable rate of T. cruzi seropositivity (Davila Rosenthal et al, 2016). Furthermore, another study found that only one-third of deaths in CD patients were directly related to the disease, with neoplasms being the leading cause of death (Ramos-Rincon et al, 2021). Interestingly, a related study on CD mortality by Santo (2009) identified neoplasms as one of the primary underlying causes of death, although a comparative analysis with healthy individuals was absent.…”
Section: T Cruzi Chagas Disease and Cancer: The Paradox Unveiledmentioning
confidence: 99%